A CONCEPTUAL DESIGN OF CLOUD-BASED AUTONOMOUS GROUND VEHICLE ROBOT NAVIGATION CONTROL FOR IR4.0 APPLICATIONS - Muhammad Amzie Muhammad Fauzi; Shafrida Sahrani; Mohamad Hanif Md Saad; Sallehuddin Mohamed Haris; Muhd Zamry Abu Samah, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Autonomous Ground Vehicle (AGV) type robots are increasingly used in numerous applications nowadays, including as service robots attending to customers in restaurants and shops. They can also seeing increasing applications as surveillance robots. One of the problems the operators of such robots faced is when they need to precisely control the movement of the robot to inspect the robots surrounding over the internet. In this paper, we describe a preliminary design and implementation of a cloud-based navigation control systems for AGV type robots. This allows remote robot supervisors to navigate the robot for precise local positioning over the Internet. The robot’s communication system uses the ThingsSentral cloud-based IOT platform to enable communication and navigation control between remote robot supervisor and the local robot over the Internet. The robot’s navigation process also involves the use of ultrasonic sensor for assisting local navigation of the robot, assisting the robot’s safety system to protect it from unforeseeable accidents. The overall prototype system was designed, developed and tested successfully in this project.